2014
DOI: 10.1371/journal.pone.0093855
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of French GPs to Chronic Neuropathic Pain Clinical Guidelines: Results of a Cross-Sectional, Randomized, “e” Case-Vignette Survey

Abstract: Background and aimsThe French Pain Society published guidelines for neuropathic pain management in 2010. Our aim was to evaluate the compliance of GPs with these guidelines three years later.MethodsWe used “e” case vignette methodology for this non interventional study. A national panel of randomly selected GPs was included. We used eight “e” case-vignettes relating to chronic pain, differing in terms of the type of pain (neuropathic/non neuropathic), etiology (cancer, postoperative pain, low back pain with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
(38 reference statements)
0
19
0
1
Order By: Relevance
“…6 In contrast, a recent large study of general practitioners’ adherence to current French recommendations observed a paucity of appropriate recall of first-line drugs. 8 One important educational objective of the present guidelines will be to facilitate their dissemination and subsequently assess their real life implementation in various countries. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In contrast, a recent large study of general practitioners’ adherence to current French recommendations observed a paucity of appropriate recall of first-line drugs. 8 One important educational objective of the present guidelines will be to facilitate their dissemination and subsequently assess their real life implementation in various countries. 7 …”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 This may be due to lack of diagnostic accuracy and relatively ineffective drugs, but also insufficient knowledge about effective drugs and their appropriate use in clinical practice. 8 Evidence-based recommendations for the pharmacotherapy of neuropathic pain are therefore essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, prior studies have found limited adherence by physicians to guideline recommendations for the use of opioids to manage chronic pain [5,6], explained in part by lack of awareness and familiarity with guidelines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies state that many patients with NP do not receive appropriate treatment for their pain [47] possibly due to the lack of diagnosis and relatively ineffective drugs. The clinician's lack of knowledge about NP medications and their appropriate use in clinical practice augments this problem [48]. The use of diagnostic algorithms for NP [38] and screening tools [32] should contribute to reducing diagnostic heterogeneity.…”
Section: Challenges In the Pharmacological Management Of Neuropathic mentioning
confidence: 99%